Abortion access in the Americas: a hemispheric and historical approach - Roth, Cassia (Frontiers in Public Health, 2023)
This perspective article situates the 2022 United States (U.S.) Supreme Court’s overturning of Roe v. Wade (1973) within the broader history of abortion rights activism and legislation in the greater Americas. The U.S. public has stereotyped Latin America and the Caribbean (LAC) as socially conservative regarding gender issues and anti-reproductive rights. But twenty-first-century LAC presents a more complicated landscape than this dominant narrative suggests. In the past 15 years, political, legislative, and public health advances and setbacks across the region provide both a blueprint for re-establishing access to safe and legal abortion and a warning on the consequences of the criminalization of abortion for the U.S. Employing a narrative approach that summarizes recent interdisciplinary literature, this perspective traces the history of the expansion of abortion access in the Americas. Mexico (2007, 2023), Uruguay (2012), Argentina (2020), and Colombia (2022) legalized abortion on demand within specific timeframes. These expansions coexist with severe restrictions on abortion in various nations including Haiti (1835), the Dominican Republic (1884, 2009), Honduras (1985, 2021), El Salvador (1997), and Nicaragua (2006), as well as some states in the United States (2022). This perspective finds that legalization occurs when feminist activists eschew U.S.-based feminist rhetoric of individual rights and choice to reframe abortion as a form of gender-based violence within a discourse of health and wellbeing as a human right. According to this perspective, restrictions on access to the procedure constitute a form of violence against women and people capable of bearing children and violate human rights.